Intensity and prevalence of ectoparasites infesting Indonesian mangrove crabs (Scylla serrata): A study in Banda Aceh, Indonesia - Nisa, Nurian; Akbar, Said A.; Perdana, Adli W.; Aleid, Layan KM.; Wikurendra, Edza A. (Narra Sains Indonesia, 2024)
Mangrove crab (Scylla serrata) is a fishery commodity that has high economic value. The supply of mangrove crabs in Indonesia is still dominated by wild catches. One of the places to catch mangrove crabs is in the Mangrove Area of ​​Deah Raya Village, Syiah Kuala District, Banda Aceh, Indonesia. Mud crabs are very susceptible to infestation by pathogens in their environment. Pathogens that are often found infesting mud crabs are parasites. Ectoparasite attacks are very dangerous for mud crabs because they can damage the body organs of mud crabs. Therefore, this research was conducted to determine the level of intensity and prevalence of ectoparasites in mud crabs (S. serrata) caught by fishermen in Deah Raya Village. This research uses a survey method with a purposive sampling method. Ectoparasite examination is carried out using the smear method. This research was conducted at the Hatchery Laboratory of the Faculty of Maritime Affairs and Fisheries in May 2024. Thirty crabs (S. serrata) were randomly sampled from the mangrove area in ​​Deah Raya Village, Syiah Kuala District, and observed for the presence of ectoparasites. The observations revealed that the crabs were infested by ectoparasites from the protozoa phylum (such as Zoothamnium sp., Epistylis sp., and Vorticella sp.) and from the arthropod phylum (Octolasmis sp.). Infestation by Zoothamnium sp. was found as the most prevalent (n=15, 50%), followed by Epistylis sp. (n=6, 20%), Vorticella sp (n=3, 10%), and Octolasmis sp (n=3, 10%). The infestation intensity for Zoothamnium was 7.5 individuals per crab, Epistylis sp. 5.0 individuals per crab, Vorticella sp. 2 individuals per crab, and Octolasmis sp. 1 individual per crab. Considering the high prevalence and intensity of Zoothamnium sp. in the mangrove crabs, the mitigating efforts can be focused on this ectoparasite.